Current perspectives on female offending - De Coster, Stacy (Gender and crime, 2024)
This chapter traces the development of contemporary feminist theories of offending. We show how integrating feminist perspectives with mainstream criminological frameworks expanded our understanding of women’s offending and the gender gap in crime. However, we argue that theorizing about gender and crime more broadly is more productive when we engage with feminist perspectives as our theoretical starting point. We focus specifically on frameworks that articulate gender as a situational accomplishment and describe gendered pathways of criminal legal system contact. These perspectives reveal how structural power arrangements and cultural gender schemas shape interactions, identities, emotions, and behavioral repertoires. They also highlight the need to consider the complex interplay between victimization, offending, and criminal legal system experiences in theories of gender and crime. We conclude with a plea for criminology to preference theories that integrate core insights across strands of feminist and intersectional theorizing to generate a more nuanced and robust theoretical landscape.